Contribution to the knowledge of the palynology of Rhynchocorys and its systematic significance - Kursat, Murat; Sancar, Pelin Yilmaz; Demirpolat, Azize; Baser, Birol; Civelek, Semsettin (Taylor & Francis Inc, 2026)
Pollen grains of seven taxa of Rhynchocorys Griseb. (Orobanchaceae) were investigated using light and scanning electron microscopy to determine their properties and assess their taxonomic significance. The overall shape of Rhynchocorys pollen grains is shown here. The pollen grains are monads, radially symmetrical, and isopolar. The basic shape of the pollen grains was prolate-spheroidal, oblate-spheroidal, and subprolate; the aperture is tricolporate. Three major sculpturing patterns of exine are observed: microperforate, retipilate, and granulate. Principal component analysis (PCA) and the unweighted pair group method using arithmetic average (UPGMA) analyses demonstrate that pollen dimensions and exine sculpturing are effective diagnostic variables for distinguishing Rhynchocorys taxa. However, they do not contribute significantly to sectional distinctions. In the present study, the pollen morphology of Rhynchocorys is analyzed for the first time. The Rhynchocorys genus, which is represented by seven species worldwide, is fully represented by all its taxa in T & uuml;rkiye.
Keywords: Electron microscope; light microscope; PCA; Rhynchocorys